Peripheral plasma levels of progesterone and oestradiol-17B of West African Dwarf goats during the oestrous cycle - Akusu, M.O.; Nduka, E.; Soyebo, B.A. (1992)
Oestrus was synchronised with PGF2-alpha in four pluriparous West African Dwarf (WAD) goats and blood collected through jugular venupuncture. The length of the oestrous cycle and oestrus duration were observed in three successive cycles while peripheral plasma progesterone and oestradiol-17B levels were determined by the radioimmunoassay technique. The mean oestrous cycle lengths and oestrus duration were 19.4 ± 1.7 d and 33.3 ± 6.6 h, respectively. Progesterone levels were very low during the first four days of the cycle (day 1 = day of oestrous) with the lowest level of 0.3 ± 0.02 ng/ml being recorded on day 2 of the cycle. There was a steady rise in the levels during the cycle until day 15 when the highest level of 2.2 ± 0.05 ng/ml was recorded which was followed by a sharp decline on day 20 (P <0.05). The profile of oestradiol-17B was erratic during the cycle. Mean maximum and minimum concentrations were recorded on day 1 (152.6 ± 31.6 ng/ml) and day 2 (58.8 ± 22.6 ng/ml), respectively. These results showed that while progesterone and oestradiol profiles in the WAD goat followed the luteal and follicular phases of the oestrous cycle, progesterone profile is more reliable in assessing the phases of the oestrous cycle.